Seed Predation of Copaifera langsdorffii Desf. (Fabaceae: Caesalpinioideae) by Rhinochenus brevicollis Chevrolat (Coleoptera: Curculionidae) in a Brazilian Cerrado Fragment - Fagundes, Marcílio (2013)
Seed predator insects are generally highly specialized herbivores that can be affected by several plant characteristics. In this study, the resource concentration hypothesis and the plant architecture hypothesis were tested by evaluating the attack of Rhynochenus brevicollis on Copaifera langsdorffii seeds. The study was conducted in a cerrado fragment situated in southeastern Brazil. The percentage of C. langsdorffii seed predation by R. brevicollis ranged from 1 to 30% (mean±SD, 9.31±6.41). The percentage of seed predation was negatively related to the number of fruits per branch. The predation of seeds by the beetle was positively affected by plant crown circumference, while plant height did not show any relationship with seed predation. Thus, our results did not support any of the two hypotheses evaluated. Finally, the study discusses the role of plant phenology (masting) in regulating the seed predator’s population in cerrado vegetation.